Co-based MOR/ZSM-5 composite zeolites over a solvent-free synthesis strategy for improving gasoline selectivity. (1st July 2018) - Cheng, Shilin; Mazonde, Brighton; Zhang, Guihua; Javed, Mudassar; Dai, Peiyao; Cao, Yingnan; Tu, Sisi; Wu, Jiayi; Lu, Chengxue; Xing, Chuang; Shan, Shengdao
Graphical abstract: Highlights: Co@MOR/ZSM-5 zeolites was fabricated under a solvent-free synthesis method. Crystallization time was directly proportional with crystal morphology. High gasoline selectivity obtained from MOR/ZSM-5 composite crystals. Na-type zeolite decrease acidity, leading to a low isoparaffin selectivity. Abstract: Composite zeolites containing ZSM-5 are known to be very active for catalytic conversion of syngas into gasoline range hydrocarbons under Fischer-Tropsch synthesis. In this work, a novel MOR/ZSM-5 composite zeolite with immersed Co particles was successfully fabricated under a facile solvent-free synthesis method. The final catalysts were characterised by XRD, SEM and TEM procedures to evaluate the structural properties and morphologies of Co@MOR/ZSM-5. Variation in the crystallization time played a vital role during zeolite synthesis. Perfect crystal structure for solvent-free Co@MOR/ZSM-5 was found at 72 h of crystallization time and proved to exhibit the greatest gasoline selectivity of 72.3%. This composite zeolite synthesized by solvent-free method with outstanding performance, has all potential to act as highly effective heterogeneous catalyst in the near future.